Relational ethics between researchers: An Indigenous qualitative perspective - Gloria Fraser (Methods in Psychology)
Qualitative research has long emphasized the ethics of researcher-participant relationships, however far less attention has been given to the ethical complexities of relationships between research collaborators. For Indigenous researchers, research collaborations can be shaped by tokenism within academic institutions that often prioritize funding success and publication outputs over relationality. Drawing on my experiences as a Māori qualitative researcher, this commentary explores the often-overlooked ethics of researcher-researcher relationships and advocates for a relational ethics approach, grounded in Māori values of whanaungatanga (building and maintaining relationships) and manaakitanga (care, reciprocity, and collective responsibility) as central to ethical qualitative research. I reflect on the ways in which Indigenous researchers are often positioned as cultural consultants rather than full research partners, with cultural responsibilities delegated to them instead of being collectively considered within research teams. In response, I offer reflections on how qualitative researchers can cultivate meaningful, reciprocal relationships that extend beyond transactional academic norms. Taking time to build relationships before formal collaborations begin, pushing back against extractive research practices, and shifting institutional cultures to recognize relational work as valuable are all critical steps. Ultimately, I imagine a more compassionate and just academy—one that values relationships as central to ethical research and recognizes the transformational potential of decolonization in shifting what counts as success.